The Effect of Disclosing Key Audit Matters(KAM) on Audit Quality: Evidence from Chinese Listed Companies - Wang, Haoming (2019)
This paper aims at studying the impact of the audit reform (disclosing key audit matters) on audit quality in the Chinese market, where, the research about this aspect is still in its infancy that the consequence is not clear. This research firstly uses data from 3269 Chinese pure A-share listed companies and empirical approach to study the relationship between key audit matters (KAM) and audit quality. It finds that KAM is significantly negatively related with absolute discretionary accruals which can conclude that KAM has a positive effect on audit quality. This might because the disclosure of KAM can improve investors' awareness of the audit report, change the behavior of CPA in the auditing process and alter the manager’s behavior of decision-making. In addition, as A+H shares listed companies, which is a special type of A-shares listed company, are double regulated by both the Chinese mainland market and the Hong Kong market that might lead to the effects of KAM are different. With the purpose of more comprehensively explore the impact of KAM on the whole Chinese market, this type of company also be considered. Therefore, this paper also uses 68 A+H-share listed companies and 68 A-share listed companies to study the different effects of these two kinds of listed companies. It ends up with the evidence that the effect of KAM on A+ H-share listed companies is better than that on pure A-share listed companies. That may be because of stronger regulation faced by A+H share listed companies.